The policy deadlock of digitizing cable TV in Taiwan: An analytic hierarchy process on the stakeholders' interests - Yuntsai Chou (International Telecommunications Society (ITS), 2012)
This paper probes the phenomenon of delayed cable digitization in countries such as Korea and Taiwan. The paper first performed a cross-country longitudinal analysis on the 16 countries in the Asia Pacific region and found out that 1. inter-platform competition, primarily from DBS, generates the strong and positive impact on the ratio of cable digitization; 2. the analog installed base reduces the percentage of digital cable service subscribed; and 3. consumers' switching costs decrease their willingness to subscribe the digital service, therefore reduces the ratio of digitization. An AHP study of Taiwan's cable operators demonstrates the top three policy preferences as: 1. rate deregulation; 2. lifting the horizontal integration cap; and 3. the set-up-box subsidies. The results of two empirical tests together conclude that countries should deregulate the cable tariffs and encourage inter-platform competition. As rate deregulation grants the operators flexibility in charging the services, they can compensate consumers the switching costs by lower digital tariffs. For countries shich lack of budget in subsidization, they are advised to bundle rate deregulation with the operators' obligation to subsidize consumers. The countries also need to create a level playing field among various TV platform operators to entail inter-platform competition and thus a higher ratio of cable digitization.
Keywords: 330; digital switchover; inter-platform competition; network effects; switching costs; rate deregulation; analytic hierarchy process; Taiwan